Finite-time robust control for transformerless H-bridge cascaded STATCOM with star configuration. Issue 2 (3rd April 2021) - Lv, Xingyu; Lei, Bangjun; Fei, Shumin
Abstract : This article presents a finite-time robust control (FTRC) of a transformerless STATCOM based on a cascaded multilevel H-bridge converter (CMHC) with star configuration. The FTRC is first proposed for the current loop control of a CMHC-based transformerless STATCOM by using the finite time robust control theory. Taking the parameters, perturbations and external disturbances into account and using coordinate transformation method, the nonlinear dynamic model of the CMHC-based transformerless STATCOM is transformed into a standard nonlinear port-controlled dissipative Hamiltonian (PCDH) structure. Based on the PCDH structure, an FTRC is designed for the CMHC-based transformerless STATCOM to improve the transient stability and oscillation damping of power system. Finally, the simulation results demonstrate that the FTRC has better dynamic performance and strong robustness in comparison with the passivity-based control of the CMHC-based transformerless STATCOM.